Business acumen for strategic communicators : a primer - Ragas, Matthew W., 1977-; Culp, Ron, 1947- (Emerald Publishing Limited, 2021)
Business acumen has emerged as a critical competency for communicators. But if you're a public relations, advertising or communication professional that didn't go to business school, how can you make sure you have the abilities and skills to evolve along with your role? 'Business Acumen for Strategic Communicators' is the book for you. Offering a critical primer for the world of business, Ragas and Culp equip you with the must-have business know-how needed to understand everything from the language and thinking of C-suites and boardrooms, to organizational agility, business models, rules and regulations, the money and the numbers, and even how to read financial statements and reports. Written for communicators by communicators, the concepts in each chapter are illustrated by expert insight essays written by a diverse group of senior communications leaders, and packed full of case studies, interviews, key terms and cutting-edge research. Brands profiled include Aflac, Costco, CVS Health, Levi Strauss, Mayo Clinic, Southwest Airlines, Target and YMCA of America. With these critical business literacy skills in hand, you will be set to serve with success as strategic counselors to the organizational leaders that are your colleagues, clients, and business partners.